Deciphering the epigenetic role of KDM4A in pancreatic β-like cell differentiation from iPSCs - Arroyave, Felipe; Méndez-Castillo, Lina; Lizcano, Fernando (Frontiers in Endocrinology, 2025)
IntroductionPancreatic β cells derived from human induced pluripotent stem cells (hiPSCs) represent a promising therapeutic avenue in regenerative medicine for diabetes treatment. However, current differentiation protocols lack the specificity and efficiency required to reliably produce fully functional β cells, limiting their clinical applicability. Epigenetic barriers, such as histone modifications, may hinder proper differentiation and the acquisition of essential maturation markers in these cells.MethodshiPSCs were cultured under feeder-free conditions and subjected to lentiviral transduction with shRNA constructs to silence KDM4A. Differentiation into pancreatic β-like cells was performed using stepwise protocols, with or without doxycycline supplementation, to evaluate the effect of KDM4A suppression. Gene expression was quantified by RT-qPCR, protein expression was assessed by western blotting and immunofluorescence, and functional insulin release was determined by glucose-stimulated insulin secretion (GSIS) assays. Statistical analysis was conducted using unpaired two-tailed Student’s t-tests, with significance set at p < 0.05.ResultsA reduction in pancreatic development proteins was observed in the different differentiation states evaluated, after blocking KDM4A expression. Knockdown of KDM4A significantly reduced the expression of pancreatic β-cell genes, such as PDX1, Nkx6.1, and Ins, by 50% compared to WT iPSCs differentiated under the same conditions. Similarly, glucose-stimulated insulin secretion was reduced by approximately 80% in KDM4A-deficient β-like cells.ConclusionsThese results emphasize the critical role of histone demethylation in hiPSC differentiation toward β cells. Our findings identify KDM4A as a key epigenetic regulator, suggesting that its modulation could enhance the generation of functional β cells for regenerative medicine in diabetes.